2016
DOI: 10.1161/circep.116.004239
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Antral Isolation and Nonpulmonary Vein Trigger Ablation Are Sufficient to Achieve Favorable Long-Term Outcomes Including Transformation to Paroxysmal Arrhythmias in Patients With Persistent and Long-Standing Persistent Atrial Fibrillation

Abstract: A lthough pulmonary vein isolation (PVI) is well accepted to be the cornerstone of ablation for paroxysmal atrial fibrillation (AF), there remains lack of consensus on the optimal ablation strategy in patients with persistent and longstanding persistent AF. [1][2][3] Although an ablation strategy limited primarily to PVI, with or without targeting of documented nonpulmonary vein (PV) triggers, results in lower long-term AF-free survival rates in patients with persistent and longstanding persistent AF than paro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Consistent with our findings, the recent meta‐analysis of the PVI‐only strategy in persistent AF patients showed a single‐procedure arrhythmia‐free survival rate of 66.7% . A limited ablation strategy of PVI and ablation of only documented non‐PV triggers was also found to provide transformation from persistent to paroxysmal AF, and good long‐term AF control with a low frequency of AT in the majority of patients …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our findings, the recent meta‐analysis of the PVI‐only strategy in persistent AF patients showed a single‐procedure arrhythmia‐free survival rate of 66.7% . A limited ablation strategy of PVI and ablation of only documented non‐PV triggers was also found to provide transformation from persistent to paroxysmal AF, and good long‐term AF control with a low frequency of AT in the majority of patients …”
Section: Discussionsupporting
confidence: 89%
“…Second, residual or recurrent triggers after the ablation proce- Consistent with our findings, the recent meta-analysis of the PVI-only strategy in persistent AF patients showed a single-procedure arrhythmia-free survival rate of 66.7%. 32 A limited ablation strategy of PVI and ablation of only documented non-PV triggers was also found to provide transformation from persistent to paroxysmal AF, 33 and good long-term AF control with a low frequency of AT in the majority of patients. 34 Our data also indicated that patients with more enlarged LA diameter and with diabetes mellitus were more likely to have inducible atrial tachyarrhythmias in persistent AF.…”
Section: Electrophysiological and Pharmacological Inducibilitymentioning
confidence: 97%
“…We have recently shown that in patients with nonparoxysmal AF treated with a limited ablation strategy of antral PVI and targeting of non-PV triggers, patients who recur as paroxysmal (rather than persistent) AF type are more likely to experience long-term ablation success[49]. We believe that patients with persistent or longstanding persistent AF who experience paroxysmal-type ERAA after ablation may represent a subgroup of patients in whom early reablation (even during the blanking period) can improve long-term ablation success.…”
Section: Treatment Of Eraamentioning
confidence: 99%
“…46, 47 On the other hand, limited ablation targeting PVs and documented non-PV triggers improved the maintenance of sinus rhythm in persistent and longstanding persistent AF. 48 These results suggest that localization and ablation of documented non-PV triggers is important to improve the outcome of ablation for persistent AF.…”
Section: Discussionmentioning
confidence: 84%